Aberrant expression of miR-214 is associated with obesity-induced insulin resistance as a biomarker and therapeutic - Fangxiao Cheng; Geheng Yuan; Jiao He; Yimin Shao; Junqing Zhang; Xiaohui Guo (BMC, 2020)
Abstract Background Insulin resistance (IR) in obesity is associated with the occurrence of metabolic and cardiovascular diseases. Dipepidyl peptidase 4 (DPP4) plays a pivotal role during the development of IR, and was found to be a target gene of microRNA-214 (miR-214) in our study. This study sought to assess the expression and clinical value of miR-214 in obese patients with IR, and investigate its therapeutic potential in obese rats and adipocytes with IR. Methods Serum expression of miR-214 in obese patients with or without IR was estimated by quantitative real-time-PCR. A receiver operating characteristic curve was plotted to evaluate the diagnostic value of miR-214 in the patients. Obesity-induced IR animal and cell models were constructed, and the therapeutic ability of miR-214 was explored. Results Serum expression of miR-214 was decreased in obese patients compared with the healthy controls, and the lowest expression was observed in the cases with IR. Downregulation of miR-214 was significantly correlated with the serum DPP4 levels and HOMA-IR of the patients upon IR conditions, and was demonstrated to perform diagnostic accuracy for distinguishing obese patients with IR from those without IR. In obesity-associated IR animal and cell models, the downregulation of miR-214 was also been detected. According to the measurement of glucose and insulin tolerance and glucose uptake abilities, we found that the overexpression of miR-214 could be used to alleviate IR in the IR models, especially when collaboratively used with DPP4 inhibitor vildagliptin. Conclusion All data revealed that miR-214, as a regulator of DPP4, is decreased in obese patients with IR and may serve as a diagnostic biomarker. The upregulation of miR-214 could improve IR in obese rats and adipocytes, indicating that miR-214 has the therapeutic potential for obesity and IR.